Effects of a co-created occupational health intervention on stress and psychosocial working conditions within the construction industry: A controlled trial - Cedstrand, Emma; Augustsson, Hanna; Alderling, Magnus; Sánchez Martinez, Néstor; Bodin, Theo; Nyberg, Anna; Johansson, Gun (Frontiers in Public Health, 2022)
Background: Work-related stress problems, i.e., burnout, depression, and anxiety, is a rising global health challenge. Poor mental health also appears to be a challenge for the construction industry, even though the occupational health focus has traditionally been on the physical work environment and musculoskeletal disorders. Yet, studies targeting the organisational level (i.e., work environment, policy) to enhance mental health within the construction industry are scant. Therefore, our first objective was to evaluate the effectiveness of a co-created occupational health intervention on stress and psychosocial working conditions within the construction industry in Sweden. The second objective was to assess whether the intervention was implemented as intended, i.e., implementation fidelity. The trial is registered in the ISRCTN clinical trial registry (ISRCTN16548039, http://isrctn.com/) Methods: This is a controlled trial with one intervention and one matched control group. We co-created the program logic with stakeholders from the intervention group. The essence of the chosen intervention components, duties clarification, and structured roundmaking was enhanced planning and role clarification. We assessed adherence to the intervention and dose delivered (i.e., fidelity). We collected data on the outcomes (role clarity, team effectiveness, planning, staffing, quantitative demands, and the psychosocial safety climate) with online questionnaires at baseline, 12, and 24 months. Marginal means models adjusting for missing data patterns were applied to estimate potential differences in outcomes between groups over time. Results: Fidelity was considered reasonably high. Yet, we found no intervention effects on the primary outcome stress. All outcomes, except role clarity, deteriorated during the trial in the intervention and control group. However, the results indicate a positive effect of the intervention components on professionals’ role clarity. The pandemic appears to have negatively affected stress and psychosocial working conditions. Conclusion: The study’s results suggest that co-creating occupational health interventions could be one solution for improved implementation fidelity. More studies are needed to evaluate these intervention components. Also, we recommend researchers of future intervention studies consider using missing not at random, sensitivity analysis.